Dziadek do orzechow - Hoffmann, E. T. A. (Ernst Theodor Amadeus), 1776-1822.; Kramsztyk, Jozef; Kuliczkowska, Krystyna; Szancer, Jan Marcin, 1902-1973. (Warszawa : Ksiazka i Wiedza, 1989)
The fairy tale about the nutcracker who turns into a handsome prince and helps fight the Mouse King. A translation of Hoffmann's tale. Ages 6-10.
Translation of: Nussknacker und Mausekonig.
Keywords: Toys -- Juvenile fiction